MXene-coated COF composite material and preparation method and application thereof

By combining MXene nanosheets with covalent organic framework (COF), the MXene@COF composite material is formed, which solves the problem of poor dispersion in hydrogels, and achieves high toughness and strong electromagnetic shielding performance under extremely low conductive content .

CN119463398APending Publication Date: 2025-02-18GUIZHOU MINZU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586156.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

Smart Images

  • Figure CN119463398A_ABST
    Figure CN119463398A_ABST
Patent Text Reader

Abstract

The invention discloses an MXene (at) COF composite material as well as a preparation method and application thereof, and belongs to the technical field of preparation of electromagnetic wave shielding materials. The preparation method of the MXene (at) COF composite material comprises the following steps: slowly adding LiF and Ti3AlC2 into an HCl solution, heating, stirring, centrifugally washing until the pH value of supernate is 6, and carrying out ultrasonic treatment, centrifugation and freeze drying in an N2 atmosphere; performing ultrasonic dispersion, adding p-phenylenediamine, performing ultrasonic mixing, heating and stirring; the preparation method comprises the following steps: adding 2, 4, 6-triformyl phloroglucinol and p-phenylenediamine, heating and stirring, washing, and freeze-drying; dissolving the MXene coated COF composite material in an acrylamide and gelatin blended solution, adding an initiator and a cross-linking agent, and heating to obtain the MXene coated COF composite material. The MXene (at) COF composite material disclosed by the invention has high toughness and strong electromagnetic shielding performance under the condition of extremely low content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electromagnetic wave shielding material preparation, and specifically relates to a MXene@COF composite material and a preparation method and application thereof. Background Art

[0002] As a porous material, hydrogel has attracted much attention due to its adaptability to any shape and self-healing ability. Its internal network is rich in water groups, which have a certain loss capacity for electromagnetic waves, making hydrogels show a wide range of application potential in wearable electronics, aerospace, and electromagnetic shielding. However, pure hydrogels lack conductivity and electromagnetic shielding effects, and these properties need to be improved by adding functional fillers.

[0003] At present, there are various preparation strategies for electromagnetic shielding hydrogels, among which polyvinyl alcohol and polyacrylamide hydrogels are the most common. Polyacrylamide, as a hydrophilic polymer, is formed by free radical polymerization of acrylamide. Its internal cross-linked network contains reactive groups such as amide bonds, which are conducive to the formation of hydrogen bonds and chemical modification, and has a short preparation cycle. However, the mechanical properties and stability of a single hydrogel are poor, so gelatin is introduced to construct a double network hydrogel to enhance its mechanical properties.

[0004] In addition, two-dimensional transition metal carbides and / or nitrides (MXenes) show special advantages in the field of hydrogel flexible sensing due to their high conductivity, abundant active sites (such as -OH, -F, -O, etc.), electrochemical behavior and unique hydrophilicity. However, due to the strong van der Waals interaction between MXene nanosheets, aggregation and self-stacking easily occur, resulting in poor dispersion when MXene nanosheets are made into hydrogels alone. MXene clusters and self-stacking in the internal network of hydrogels limit their application potential in hydrogels. Therefore, how to improve the dispersion of MXene nanosheets in hydrogels is a key challenge to improve their application performance. Summary of the invention

[0005] The present invention aims to provide a MXene@COF composite material and a preparation method and application thereof. The MXene@COF composite material has high toughness and strong electromagnetic shielding performance at an extremely low content.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a MXene@COF composite material comprises the following steps:

[0008] S1. Preparation of MXene nanosheets: LiF and Ti3AlC2 were slowly added to a HCl solution, heated and stirred, and the solution was transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant was 6. Ultrasonication was performed under a N2 atmosphere, and the suspension was centrifuged to obtain a MXene suspension, which was freeze-dried to obtain MXene nanosheets.

[0009] S2. Preparation of MXene-NH2: ultrasonically dispersing the MXene nanosheets obtained in step S1 in a 99.7% ethanol solution, adding p-phenylenediamine, ultrasonically mixing, heating and stirring, collecting the product, and obtaining MXene-NH2;

[0010] S3, ultrasonically dispersing the MXene-NH2 obtained in step S2 in a 99.7% ethanol solution, adding 2,4,6-triformylphloroglucinol and p-phenylenediamine, heating and stirring, washing with anhydrous ethanol, and freeze-drying to obtain MXene@COF;

[0011] S4. Dissolve the MXene@COF obtained in step S3 in a blended solution of acrylamide and gelatin, add an initiator and a cross-linking agent, and heat to obtain a MXene@COF composite material.

[0012] Preferably, in step S1, LiF and Ti3AlC2 are slowly added to the HCl solution, heated and stirred at 30-45°C for 36 hours, and the solution is transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant is 6.

[0013] Preferably, in step S1, under N2 atmosphere, 40KHz ultrasound is used for 30 minutes, and centrifugation is performed at 3500rpm for 1 hour to obtain a MXene suspension, which is freeze-dried at -85°C to obtain MXene nanosheets.

[0014] Preferably, in step S2, the process parameters of the ultrasonic dispersion are as follows: ultrasonic frequency is 40 kHz, and ultrasonic time is 30 min.

[0015] Preferably, in step S2, p-phenylenediamine is added, ultrasonic mixing is performed at 40 kHz for 10 min, heating and stirring are performed at 80-90° C. for 50 min, and the product is collected to obtain MXene-NH2.

[0016] Preferably, in step S3, the process parameters of the ultrasonic dispersion are as follows: ultrasonic frequency is 40 kHz, and ultrasonic time is 60 min.

[0017] Preferably, in step S3, 2,4,6-triformylphloroglucinol and p-phenylenediamine are added, heated and stirred at 80-90° C. for 24 h, washed with anhydrous ethanol, and freeze-dried at -85° C. to obtain MXene@COF.

[0018] Preferably, in step S4, the MXene@COF obtained in step S3 is dissolved in a blended solution of acrylamide and gelatin, an initiator and a cross-linking agent are added, and the mixture is heated at 58-62° C. for 4 h to obtain a MXene@COF composite material.

[0019] Preferably, the initiator is ammonium persulfate; and the cross-linking agent is N,N'-methylenebisacrylamide.

[0020] Preferably, MXene@COF powder is mixed with acrylamide and gelatin to prepare a MXene@COF composite material with a thickness of 2 to 3 mm.

[0021] The present invention also provides a MXene@COF composite material prepared by the preparation method as described.

[0022] The present invention also provides a MXene@COF composite material prepared by the preparation method or use of the MXene@COF composite material in electromagnetic shielding.

[0023] Compared with the prior art, the present invention has the following advantages and technical effects:

[0024] The present invention introduces a MXene@COF composite material and its preparation method and application. This technology successfully maintains the two-dimensional characteristics of MXene by preparing a MXene@COF heterostructure, and the outer COF layer effectively prevents the aggregation and self-stacking of MXene nanosheets. This structure not only increases the porosity of the material, but also significantly improves its conductive properties. The MXene@COF material is dissolved in polyacrylamide and gelatin hydrogel, and an initiator and a cross-linking agent are added to induce acrylamide to undergo free radical polymerization at a specific temperature to prepare a hydrogel. MXene@COF and the hydrogel are cross-linked through dynamic bonds such as hydrogen bonds and intermolecular forces to produce a stable cross-linked structure, which gives the hydrogel electromagnetic shielding properties. In addition, by adjusting the concentration of COF, the electromagnetic shielding properties of the hydrogel can be precisely controlled.

[0025] The COF coating not only improves the aggregation and self-stacking problems of MXene nanosheets, but also enhances their conductivity. This MXene@COF composite material can show high toughness and strong electromagnetic shielding performance even at extremely low conductivity content. This innovative technology provides new possibilities for the development of high-performance electromagnetic shielding materials, especially in application scenarios that require light weight, high toughness and excellent electromagnetic shielding effects, such as wearable electronic devices and aerospace fields.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the hydrogel prepared in Example 1, with a scale of 10 μm;

[0028] Figure 2 This is a scanning electron microscope image of the MXene@COF nanosheet obtained in Example 2, with a scale of 5 μm;

[0029] Figure 3 This is a scanning electron microscope image of the MXene@COF composite material prepared in Example 2, with a scale of 10 μm;

[0030] Figure 4 This is a scanning electron microscope image of the MXene@COF composite material prepared in Example 3, with a scale of 5 μm;

[0031] Figure 5 This is a scanning electron microscope image of the MXene@COF composite material prepared in Example 4, with a scale of 5 μm;

[0032] Figure 6 The conductivity-resistivity diagram of the hydrogel prepared in Examples 1-4;

[0033] Figure 7 This is a graph of the electromagnetic shielding efficiency of the hydrogels prepared in Examples 1-4;

[0034] Figure 8 This is a graph showing the average electromagnetic shielding performance of the hydrogels prepared in Examples 1-4. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0036] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0037] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in the art and can be purchased through commercial channels.

[0038] Embodiment 1 This embodiment provides a hydrogel, and the preparation method comprises the following steps:

[0039] A 20% mass fraction acrylamide and gelatin blend solution was prepared, wherein the molar ratio of acrylamide to gelatin was 10:1, 0.05 g of ammonium persulfate and 0.015 g of N,N'-methylenebisacrylamide were added, and after being fully dissolved, the solution was poured into a corresponding mold, sealed with an experimental plastic wrap, allowed to stand, and heated at 60°C for 4 h to obtain a hydrogel.

[0040] Example 2 This example provides a MXene@COF composite material, and the preparation method includes the following steps:

[0041] S1. Preparation of MXene nanosheets: 1 g LiF and 1 g Ti3AlC2 were slowly added to 40 mL 9 mol / L HCl solution, heated and stirred at 35 °C for 36 h, the solution was transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant was 6, ultrasonicated at 40 KHz for 30 min under N2 atmosphere, centrifuged at 3500 rpm for 1 h to obtain a MXene suspension, and freeze-dried at -85 °C to obtain MXene nanosheets;

[0042] S2. Preparation of MXene-NH2: Disperse 20 mg of the MXene nanosheets obtained in step S1 in 20 mL of 99.7% ethanol solution at 40 kHz for 30 min, add 0.03 mM p-phenylenediamine, mix at 40 kHz for 10 min, heat and stir at 90°C for 50 min, collect the product, and obtain MXene-NH2.

[0043] S3, 20 mg of MXene-NH2 obtained in step S2 was dispersed in 20 mL of 99.7% ethanol solution by 40 kHz ultrasonic dispersion for 60 min, 0.02 mM 2,4,6-triformylphloroglucinol and 0.03 mM p-phenylenediamine were added, heated and stirred at 90 ° C for 24 h, washed with anhydrous ethanol, and freeze-dried at -85 ° C to obtain MXene@COF;

[0044] S4. The MXene@COF obtained in step S3 was dispersed ultrasonically at 40kHz for 30 minutes in 10mL of deionized water, dissolved in a 20% mass fraction of acrylamide and gelatin blend solution, wherein the molar ratio of acrylamide to gelatin was 10:1, 0.05g of ammonium persulfate and 0.015g of N,N'-methylenebisacrylamide were added, the solution was poured into the corresponding mold, sealed with experimental plastic wrap, allowed to stand, and heated at 60°C for 4h to obtain a MXene@COF composite material.

[0045] Example 3 This example provides a MXene@COF composite material, and the preparation method includes the following steps:

[0046] S1. Preparation of MXene nanosheets: 1 g LiF and 1 g Ti3AlC2 were slowly added to 40 mL 9 mol / L HCl solution, heated and stirred at 35 °C for 36 h, the solution was transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant was 6, ultrasonicated at 40 KHz for 30 min under N2 atmosphere, centrifuged at 3500 rpm for 1 h to obtain a MXene suspension, and freeze-dried at -85 °C to obtain MXene nanosheets;

[0047] S2. Preparation of MXene-NH2: Disperse 20 mg of the MXene nanosheets obtained in step S1 in 20 mL of 99.7% ethanol solution at 40 kHz for 30 min, add 0.15 mM p-phenylenediamine, mix at 40 kHz for 10 min, heat and stir at 90°C for 50 min, collect the product, and obtain MXene-NH2.

[0048] S3, 20 mg of MXene-NH2 obtained in step S2 was dispersed in 20 mL of 99.7% ethanol solution by 40 kHz ultrasonic dispersion for 60 min, 0.1 mM 2,4,6-triformylphloroglucinol and 0.15 mM p-phenylenediamine were added, heated and stirred at 90 ° C for 24 h, washed with anhydrous ethanol, and freeze-dried at -85 ° C to obtain MXene@COF;

[0049] S4. The MXene@COF obtained in step S3 was dispersed ultrasonically at 40kHz for 30 minutes in 10mL of deionized water, dissolved in a 20% mass fraction of acrylamide and gelatin blend solution, wherein the molar ratio of acrylamide to gelatin was 10:1, 0.05g of ammonium persulfate and 0.015g of N,N'-methylenebisacrylamide were added, the solution was poured into the corresponding mold, sealed with experimental plastic wrap, allowed to stand, and heated at 60°C for 4h to obtain a MXene@COF composite material.

[0050] Example 4 This example provides a MXene@COF composite material, and the preparation method includes the following steps:

[0051] S1. Preparation of MXene nanosheets: 1 g LiF and 1 g Ti3AlC2 were slowly added to 40 mL 9 mol / L HCl solution, heated and stirred at 35 °C for 36 h, the solution was transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant was 6, ultrasonicated at 40 KHz for 30 min under N2 atmosphere, centrifuged at 3500 rpm for 1 h to obtain a MXene suspension, and freeze-dried at -85 °C to obtain MXene nanosheets;

[0052] S2. Preparation of MXene-NH2: Disperse 20 mg of the MXene nanosheets obtained in step S1 in 20 mL of 99.7% ethanol solution at 40 kHz for 30 min, add 1.5 mM p-phenylenediamine, mix at 40 kHz for 10 min, heat and stir at 90°C for 50 min, collect the product, and obtain MXene-NH2.

[0053] S3, 20 mg of MXene-NH2 obtained in step S2 was dispersed in 20 mL of 99.7% ethanol solution by 40 kHz ultrasonic dispersion for 60 min, 1 mM 2,4,6-triformylphloroglucinol and 1.5 mM p-phenylenediamine were added, heated and stirred at 90 ° C for 24 h, washed with anhydrous ethanol, and freeze-dried at -85 ° C to obtain MXene@COF;

[0054] S4. The MXene@COF obtained in step S3 was dispersed ultrasonically at 40kHz for 30 minutes in 10mL of deionized water, dissolved in a 20% mass fraction of acrylamide and gelatin blend solution, wherein the molar ratio of acrylamide to gelatin was 10:1, 0.05g of ammonium persulfate and 0.015g of N,N'-methylenebisacrylamide were added, the solution was poured into the corresponding mold, sealed with experimental plastic wrap, allowed to stand, and heated at 60°C for 4h to obtain a MXene@COF composite material.

[0055] The effects of the composite materials provided in the above-mentioned Examples 1-4 were verified by the following tests.

[0056] 1. Scanning electron microscope test: After the composite material sample was sprayed with gold at room temperature and air humidity of 50%-60%, the morphology of the composite material sample was observed using a Quanta FEG 250 scanning electron microscope. The results are as follows Figure 1-5 .

[0057] Depend on Figure 1 It can be seen that the surface of the composite material prepared in Example 1 is relatively smooth when no conductive filler is added. Figure 2 This is the MXene@COF heterostructure prepared in Example 2, indicating that the MXene is aminated and the surface amine groups of the MXene-NH2 are used as reaction sites, so that the COF is well wrapped around the MXene. Figure 3 It can be seen that the internal structure of the composite material prepared in Example 2 has both flaky MXene nanosheets and fibrous COF surrounding the MXene, and exhibits a certain layered structure. Figure 4 It can be seen that the composite material in Example 3 has a large number of porous structures, which greatly increases the electromagnetic shielding performance of the material. Figure 5 It can be seen that the composite material in Example 4 also has some porous structures, but compared Figure 4 Its pore size is smaller.

[0058] 2 Conductivity test: The samples were cut into rectangular strips with a length of 10 mm, a width of 3.5 mm, and a thickness of 1 mm. The four-probe tester (RK-YA, China) was used: a commonly used conductivity measurement device. According to national standards, it was operated at 5 V, a temperature of 10-13 ° C, a relative humidity of 45%-50%, and a spacing of 2.35 mm between each contact. The test was conducted at room temperature, and each sample was tested at least three times. The results are shown in the figure. Figure 6 .

[0059] Depend on Figure 6 It can be seen that the conductivity of the composite material provided in Example 1 is 0.315s / m and the resistivity is 3.1746Ω / m. The conductivity of the composite material provided in Example 2 is 0.854s / m and the resistivity is 1.172Ω / m. The conductivity of the composite material provided in Example 3 is 1.221s / m and the resistivity is 0.819Ω / m. The conductivity of the composite material provided in Example 4 is 1.035s / m and the resistivity is 0.967Ω / m.

[0060] 3. Electromagnetic shielding performance test: The EMI test instrument used is a vector network analyzer (N5225B, Keysight, China), and the electromagnetic interference shielding effectiveness (EMI SE) is estimated in the X-band (8.2-12.4GHz). The test sample size is 10mm long, 3.5mm wide, and 3mm thick. The scattering parameters S11 and S21 are obtained, and then the electromagnetic shielding performance is calculated using the formula. The results are as follows Figure 7 and Figure 8 .

[0061] Depend on Figure 7 and Figure 8 It can be seen that the electromagnetic shielding efficiency of the composite material provided in Example 1 gradually increases with the increase of frequency in the X-band (8.2 Hz to 12.4 Hz), and the maximum value can reach 28.62 dB. T ) performance is 24.96dB. On this basis, the conductivity and electromagnetic shielding performance of the composite material are improved by adding conductive filler MXnen@COF. The electromagnetic shielding efficiency of the composite material provided in Example 2 gradually increases with the increase of frequency in the X-band, and can reach a maximum of 31.98dB. Its average electromagnetic shielding (SE T ) performance is 27.59dB. Compared with the composite material of Example 1, its electrical conductivity and electromagnetic shielding are improved.

[0062] The electromagnetic shielding efficiency of the composite material provided in Example 3 gradually increases with the increase of frequency in the X-band, and can reach a maximum of 37.52 dB. T) performance is 32.01dB. Compared with the composite material of Example 2, the electrical conductivity and electromagnetic shielding performance of the composite material at this ratio are improved. This is because when a lower p-phenylenediamine concentration (0.02mM) is used to functionalize the MXene nanosheets, the obtained MXene-NH2 (0.03mM) may lack growth sites to uniformly grow COF, so it is impossible to achieve a clear heterogeneous interface in MXene@COF, resulting in its general electrical conductivity and electromagnetic shielding performance.

[0063] The electromagnetic shielding efficiency of the composite material provided in Example 4 gradually increases with the increase of frequency in the X-band, and can reach a maximum of 34.51 dB. T ) performance is 29.62 dB. Compared with the composite material of Example 2, the electrical conductivity and electromagnetic shielding performance of the composite material at this ratio are improved, but its performance is worse than that of the composite material of Example 3. This is because the excessive COF causes the formed MXene@COF to be wrapped by a large amount of COF, and the layer is thicker, which will be not conducive to the entry and absorption of electromagnetic waves.

[0064] In summary, the present invention wraps a covalent organic framework COF on MXene, forming an optimized MXene@COF heterogeneous interface, effectively preventing MXene aggregation and self-stacking, inheriting the excellent conductivity of MXene and the porous structure of COF, and adding it to a double network composite material prepared based on thermally initiated free radical polymerization, which not only gives the composite material conductivity, but also gives it high toughness and strong electromagnetic shielding performance. Among them, after adding the conductive filler MXene@COF made of different COF concentrations, the conductivity is 0.315s / m~1.035s / m, and the average electromagnetic shielding performance in the X-band is 24.96dB~32.01dB, which far meets the commercialization needs and lays a good foundation for COF-based electromagnetic shielding materials.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a MXene@COF composite material, characterized in that: The steps include: S1. Preparation of MXene nanosheets: LiF and Ti3AlC2 were slowly added to a HCl solution, heated and stirred, and the solution was transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant was 6. Ultrasonication was performed under a N2 atmosphere, and the suspension was centrifuged to obtain a MXene suspension, which was freeze-dried to obtain MXene nanosheets. S2. Preparation of MXene-NH2: ultrasonically dispersing the MXene nanosheets obtained in step S1 in a 99.7% ethanol solution, adding p-phenylenediamine, ultrasonically mixing, heating and stirring, collecting the product, and obtaining MXene-NH2; S3, ultrasonically dispersing the MXene-NH2 obtained in step S2 in a 99.7% ethanol solution, adding 2,4,6-triformylphloroglucinol and p-phenylenediamine, heating and stirring, washing with anhydrous ethanol, and freeze-drying to obtain MXene@COF; S4. Dissolve the MXene@COF obtained in step S3 in the mixed solution of acrylamide and gelatin, add an initiator and a cross-linking agent, and heat to obtain a MXene@COF composite material.

2. The preparation method according to claim 1, characterized in that: In step S1, LiF and Ti3AlC2 are slowly added to the HCl solution, heated and stirred at 30-45°C for 36 hours, and the solution is transferred to a centrifuge tube for centrifugal washing until the pH value of the supernatant is 6.

3. The preparation method according to claim 1, characterized in that: In step S1, ultrasonic treatment was performed at 40 kHz for 30 min under N2 atmosphere, and centrifugation was performed at 3500 rpm for 1 h to obtain a MXene suspension, which was then freeze-dried at -85°C to obtain MXene nanosheets.

4. The preparation method according to claim 1, characterized in that: In step S2, the process parameters of the ultrasonic dispersion are as follows: ultrasonic frequency is 40 kHz, and ultrasonic time is 30 min.

5. The preparation method according to claim 1, characterized in that: In step S2, p-phenylenediamine was added, ultrasonic mixing was performed at 40 kHz for 10 min, heating and stirring were performed at 80-90° C. for 50 min, and the product was collected to obtain MXene-NH2.

6. The preparation method according to claim 1, characterized in that: In step S3, the process parameters of the ultrasonic dispersion are as follows: ultrasonic frequency is 40 kHz, and ultrasonic time is 60 min.

7. The preparation method according to claim 1, characterized in that: In step S3, 2,4,6-triformylphloroglucinol and p-phenylenediamine were added, heated and stirred at 80-90°C for 24 h, washed with anhydrous ethanol, and freeze-dried at -85°C to obtain MXene@COF.

8. The preparation method according to claim 1, characterized in that: In step S4, the MXene@COF obtained in step S3 is dissolved in a blended solution of acrylamide and gelatin, an initiator and a cross-linking agent are added, and the mixture is heated at 58-62° C. for 4 h to obtain a MXene@COF composite material.

9. The MXene@COF composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the MXene@COF composite material prepared by the preparation method according to any one of claims 1 to 8 or the MXene@COF composite material according to claim 9 in electromagnetic shielding.